Investigating adults with early-onset epilepsy and intellectual or physical disability. Issue 2 (24th January 2019) - Nashef, Lina; Singh, Rinki; Moran, Nicholas; Murphy, Elaine
Abstract : This article focuses on investigating adults with early-onset epilepsy and intellectual or physical disability within adult neurology services. We aim to guide general neurologists in the diagnostic reassessment of people with epilepsy and complex neurological problems of unknown cause. Following an overview, we address imaging, electroencephalography, genetic studies and metabolic testing, and give examples where diagnosis directly influences treatment. Aetiological diagnosis serves to inform prognosis, guide treatment and provide a framework for genetic counselling